Youth Responsibility in Making the World Liveable: A Theological Perspective - Luke Emehiele Ijezie (Journal La Sociale, 2021)
The task of making the world a more liveable place is the responsibility of all in the society. The young people have the special role in this responsibility because they are the future of every society and constitute its most vibrant workforce. This essay reflects from a theological perspective on this special responsibility of the youth in the contemporary society. It examines the immense potentials of being young and explains how the young people can use these potentials to bring about positive change in the society